2010
DOI: 10.1016/j.chroma.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Identification and quantification of phosphatidylcholines containing very-long-chain polyunsaturated fatty acid in bovine and human retina using liquid chromatography/tandem mass spectrometry

Abstract: The retina is one of the vertebrate tissues with the highest content in polyunsaturated fatty acids (PUFA). A large proportion of retinal phospholipids, especially those found in photoreceptor membranes, are dipolyunsaturated molecular species. Among them, dipolyunsaturated phosphatidylcholine (PC) molecular species are known to contain very-long-chain polyunsaturated fatty acids (VLC-PUFA) from the n-3 and n-6 series having 24-36 carbon atoms (C24-C36) and four to six double bonds. Recent interest in the role… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
71
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(73 citation statements)
references
References 66 publications
2
71
0
Order By: Relevance
“…Of interest is increasing evidence that suggests that the phosphorylation of ceramide to ceramide-1-phosphate regulates cell proliferation and apoptosis ( 53 ), Generally, lipid characterization by MALDI IMS in ocular tissue has been limited to mass spectra that extend to roughly m/z 900, eliminating the possibility of detecting and identifying the VLC-PUFA-containing PC lipids, which occur at very low concentrations in photoreceptors. Electrospray mass spectrometry analysis of retinas [salamander ( 29 ), rat ( 11 ), and human ( 10,24 )] has revealed the presence of VLC-PUFA-containing PC lipids, but localization of these lipids by MALDI imaging has not been presented. It is now understood that 22:6 is required for a healthy retina (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…Of interest is increasing evidence that suggests that the phosphorylation of ceramide to ceramide-1-phosphate regulates cell proliferation and apoptosis ( 53 ), Generally, lipid characterization by MALDI IMS in ocular tissue has been limited to mass spectra that extend to roughly m/z 900, eliminating the possibility of detecting and identifying the VLC-PUFA-containing PC lipids, which occur at very low concentrations in photoreceptors. Electrospray mass spectrometry analysis of retinas [salamander ( 29 ), rat ( 11 ), and human ( 10,24 )] has revealed the presence of VLC-PUFA-containing PC lipids, but localization of these lipids by MALDI imaging has not been presented. It is now understood that 22:6 is required for a healthy retina (6)(7)(8).…”
Section: Discussionmentioning
confidence: 99%
“…The normal ELOVL4 protein is responsible for elongation of LC-PUFA to VLC-PUFA found in retinal photoreceptor cells and in several other tissues ( 15,18,19,42 ). Reduced levels of C32-36 acyl PC have been found in the retina of genetic mouse models of autosomal dominant Stargardt-like macular dystrophy (STGD3) ( 43 ).…”
mentioning
confidence: 99%
“…Also, the Atlantic salmon ELOVL4 protein has been shown to effectively elongate C24-C26 polyunsaturated FAs to polyenoic products up to C36 ( 49 ). All of these fi ndings collectively in testis and sperm, or esterifi ed to the sn-1 position of phosphatidylcholine (PC) in the retina (15)(16)(17)(18)(19).…”
mentioning
confidence: 99%
“…Electrospray ionization also leads to the formation of negative ions derived from PC lipids in spite of the quaternary nitrogen atom with its permanent positive charge. Under negative Anyway, this discrepancy of abundance is not so visible when the PC molecular species contain a long-chain fatty acid linked to the sn-2 position (Berdeaux et al 2010). Kerwin, Tuininga, & Ericsson (1994) intensity are low as well as those of the fragment at 454.1 m/z arising from the loss of docohexanoyl acyl moieties.…”
Section: Phosphatidylcholine (Pc)mentioning
confidence: 99%
“…MS signals of PL are influenced by different effects related to acyl chain length, the degree of acyl chain unsaturation and concentration. Several authors (Berdeaux et al;Ahn et al 2007) have shown that the ESI-MS response increases with increasing degree of insaturation of the fatty acid side chains whereas it decreases with an increase in chain length when the phospholipids concentration range in the samples is higher than picomolar. Only the picomolar range concentration results, in fact, in a linear response.…”
Section: Detection and Quantitationmentioning
confidence: 99%